Exploratory analysis of the associations between neonicotinoids and measures of adiposity among US adults: NHANES 2015–2016. (August 2022) - Godbole, Amruta M.; Moonie, Sheniz; Coughenour, Courtney; Zhang, Cai; Chen, Aimin; Vuong, Ann M.
Abstract: Background: Toxicology studies suggest that neonicotinoids may be associated with adiposity development via thyroid hormone disruption and increased oxidative stress. Prior epidemiological studies report mixed results for the association between neonicotinoids and adiposity measures. Objective: To examine the association between detectable concentrations of parent neonicotinoids (imidacloprid, acetamiprid, clothianidin) and neonicotinoid metabolites (5-hydroxy-imidacloprid, N -desmethyl-acetamiprid) with adiposity measures among US adults, and whether sex modifies the associations for neonicotinoid metabolites with adiposity. Methods: National Health and Nutrition Examination Survey (NHANES) 2015–2016 data was utilized to estimate covariate-adjusted associations between detectable neonicotinoids and fat mass index (FMI), lean mass index (LMI), waist circumference, body fat percentage, and body mass index (BMI) using multiple linear regression. We estimated incidence rate ratios (IRRs) for overweight or obese status with detectable neonicotinoid concentrations using Poisson's modified regression. Sampling strategies were accounted for in the regression models. Results: Detectable levels of acetamiprid were associated with a decrease in FMI (β = −3.17 kg/m 2, 95% CI [-4.79, −1.54]), LMI (β = −3.17 kg/m 2, 95% CI [-5.17, −1.17]), body fat percentage (β = −4.41, 95% CI [-8.20, −0.62]), waist circumference (β = −9.80 cm, 95% CI [-19.08, −0.51]), and BMI (β = −3.88kg/m 2, 95% CI [-7.25, −0.51]) among adults. In contrast, detectable levels of 5-hydroxy-imidacloprid were associated with greater rates of being overweight/obese (IRR = 1.11, 95% CI [1.04, 1.18)) and increased LMI (β = 0.67 kg/m 2, 95% CI [0.04, 1.29]). Sex modified the association between N -desmethyl-acetamiprid and LMI ( p int  = 0.075) with a positive association among males (β = 1.14 kg/m 2, 95% CI [0.38, 1.90]), and an insignificant inverse association in females. Sex also modified the association for N -desmethyl-acetamiprid with FMI ( p int  = 0.095) and body fat percentage ( p int  = 0.072), with suggestive evidence showing positive associations for males and inverse associations for females. Conclusion: Detectable concentrations of acetamiprid were inversely associated with adiposity, while there were mixed findings for 5-hydroxy-imidacloprid. Findings suggest sex differences, though results are not clear with regard to the directionality of the association by sex. Highlights: Neonicotinoid compounds may be associated with the pathogenesis of adiposity. Acetamiprid was inversely associated with all the adiposity measures examined. 5-hydroxy-imidacloprid was positively associated with being overweight/obese. Sex differences were seen with N -desmethyl-acetamiprid and some adiposity measures.